2012
DOI: 10.1371/journal.pone.0044309
|View full text |Cite
|
Sign up to set email alerts
|

Trp RNA-Binding Attenuation Protein: Modifying Symmetry and Stability of a Circular Oligomer

Abstract: BackgroundSubunit number is amongst the most important structural parameters that determine size, symmetry and geometry of a circular protein oligomer. The L-tryptophan biosynthesis regulator, TRAP, present in several Bacilli, is a good model system for investigating determinants of the oligomeric state. A short segment of C-terminal residues defines whether TRAP forms an 11-mer or 12-mer assembly. To understand which oligomeric state is more stable, we examine the stability of several wild type and mutant TRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Although alternative folded ClyA structures cannot be excluded, the observation that ClyA oligomers with a slower electrophoretic migration form nanopores with higher conductance in lipid bilayers suggests that the three ClyA types might correspond to oligomers with different subunit stoichiometry. This is not necessarily surprising given that high order symmetrical oligomeric structures are often permissive with respect to subunit stoichiometry, 37,38 and the exact stoichiometry of E. coli ClyA (~90% sequence identity to Salmonella typhi ClyA) oligomerisation is controversial: the crystal structure (PDB_ID: 2WCD) revealed a dodecamer 36 , while earlier cryo-EM studies revealed nanopores with 8 39 or 13 40 subunits. We hypothesize that the major band on the BN-PAGE corresponding to Type I ClyA most likely represents the 12mer of the crystal structure, while the band corresponding to Type II ClyA might be the 13mer observed in earlier cryo-EM studies.…”
Section: Resultsmentioning
confidence: 99%
“…Although alternative folded ClyA structures cannot be excluded, the observation that ClyA oligomers with a slower electrophoretic migration form nanopores with higher conductance in lipid bilayers suggests that the three ClyA types might correspond to oligomers with different subunit stoichiometry. This is not necessarily surprising given that high order symmetrical oligomeric structures are often permissive with respect to subunit stoichiometry, 37,38 and the exact stoichiometry of E. coli ClyA (~90% sequence identity to Salmonella typhi ClyA) oligomerisation is controversial: the crystal structure (PDB_ID: 2WCD) revealed a dodecamer 36 , while earlier cryo-EM studies revealed nanopores with 8 39 or 13 40 subunits. We hypothesize that the major band on the BN-PAGE corresponding to Type I ClyA most likely represents the 12mer of the crystal structure, while the band corresponding to Type II ClyA might be the 13mer observed in earlier cryo-EM studies.…”
Section: Resultsmentioning
confidence: 99%
“…(MW 101,363 Da with normalized intensity as high as 10.5% compared to the 11-mer); although uncommon, small populations of TRAP 12-mers have been observed in mass spectrometry experiments 38 as well as a few solution experiments, 49,50 and in crystals. 33 In addition, we observed signals corresponding to trace dimers of TRAP11 ("double-donuts"), in agreement with previous solution experiments.…”
Section: Sources Of Errormentioning
confidence: 99%
“…Proteins symmetry research continuous to be a central theme in structural biochemistry, and some recent examples are collected in Refs. . Understanding the abundance of this structural feature—symmetry—has received much attention, because at first glance it is not clear why this feature is important for proteins function, that is, why has symmetric clustering evolved at all.…”
Section: Introductionmentioning
confidence: 99%